Management Audit of the Human Resources Function at PT.Glory Industrial Semarang I - Tsabita, Anaqoh Nisrina; Widyarti, Heni; Gunawan Putri, Alvianita (Politeknik Negeri Semarang, 2025)
Purpose: Management audit research conducted is to analyze the implementation of the existing human resource function at PT Glory Industrial Semarang I and provide recommendations on the findings of weaknesses in the human resource function. Methodology/approach: This research uses descriptive qualitative methods with data collection techniques through direct observation, interviews, questionnaires, and documentation of data related to the human resource function in PT Glory Industrial Semarang I. Results/findings: The results of the research show that PT Glory Industrial Semarang I has implemented 9 (nine) human resource functions. There are 3 (three) HR functions that have been running effectively, namely the compensation and reward system, labor protection, and labor relations. Meanwhile, 6 (six) other functions have not run effectively, namely HR planning, HR recruitment, HR selection, orientation and placement, training and development, and employee performance appraisal. Limitations: The limitation of this research is that the company does not allow researchers to access data related to human resources such as employee power and expertise, salary and bonus recaps, performance appraisal results from each department, and other confidential documents. Contribution: This research contributes to the development of management audit theory on the human resource function and helps develop a more specific evaluation model of the human resource function and can be a reference for future research.